BADANIA KLINICZNE I DOŚWIADCZALNE W CHOROBACH SERCA, PŁUC I NACZYŃAcellular biological scaffolds utilized in the preparations of heart bioprosthesis – effectiveness of different methods of acellularuzations - Wilczek, Piotr; Barańska, Anna; Kubin, Barbara; Zembala, Marian (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2009)
Introduction: Tissue engineering is a promising tool for the creation of new type of heart valve bioprothesis. Crucial for the preparations of tissue scaffolds are the optymalizations of the acellularizations methods. The intracellular matrix play both an important mechanical role, they act also as a signaling factor to induce the cell proliferations, migrations and differentiations. The acellularizations procedures have been commonly used in a tissue engineering applications to create the biological scaffold used for the preparations of heart valve bioprosthesis. But the efficiency of the acellularizations procedure depends on the methods are used and the tissue type. The type of acellularizations procedure determines both the effectivenses of cell removal and the type of extracellular matrix damage which influence the ability to use the tissue scaffold for the preparations of autologous heart valve. Aim: The aim of the study was to compare the method of valve leaflets acellularization to obtain an intact collagen scaffold valuable for autologous heart valve preparations. Material and Methods: Fresh porcine hearts obtained from slaughterhouse were transported to the laboratory in Medium 199. The pulmonary valves were dissected from the heart aseptically. The valve leaflets were divided into four groups treated as follows: 1) cyclic freezing and thawing, 2) incubation in SDS (Sodium Dodecyl Sulphate) solution following 12 h NaCl incubation, 3) 48 h incubation in Trypsin/EDTA solution, 4) SDS incubation combined with Trypsin/EDTA. All results were confirmed microscopically. After decellularization process valve leaflets were seeded with fibroblast cells clone L929 (ATCC line CCL-1), to test their growth ability. Results: After cyclic freezing and thawing process (group a) and NaCl and SDS incubation (group B) numerous cells are present in the tissue. Complete removal of cells and native collagen structure preservation were observed after SDS treatment following Trypsin/EDTA incubation (group 4). The endothelial cells seeded on the acellular tissue form the monolayer on the surface of the valve. Conclusions: The incubation of heart valve leaflets in SDS solution following Trypsin/EDTA is an efficient method to obtain acellular valve scaffold with well preserved extracellular matrix structure ideal for the autologous cell seeding study.